Single-cell RNA sequencing data from: Aberrant expression of SLAMF6 constitutes a targetable immune escape mechanism in acute myeloid leukemia - Sandén, Carl; Lilljebjörn, Henrik; Fioretos, Thoas (Lund University, 2025)
This dataset includes single-cell RNA sequencing (scRNA-seq) data from co-cultures of primary T cells and the HNT-34 AML (acute myeloid leukemia) cell line after treatment with a SLAMF6 antibody or an isotype-matched control antibody. Libraries were produced using the 10X Genomics Chromium GEM-X Single Cell 5ʹ Reagent Kits v3 and sequenced on an Illumina Novaseq 6000 system (Illumina). The dataset is available as raw sequencing reads (fastq; restricted access) or as an annotated matrix of scRNA count data (h5ad). Published in: Sandén et al, Nature Cancer, 2025: https://www.nature.com/articles/s43018-025-01054-6
Keywords: Cancer cell biology; Medical and Health Sciences; Medicin och hälsovetenskap; Cancer and Oncology; Cancer och onkologi